Pengaruh Aktivator Stardec terhadap Proses Pembuatan Pupuk Organik dari Kotoran Sapi - Tunjung Wahyu Widayati; Sri Wahyu Murni; Afika Syahliana Sriadi; Deka Prima Rosalinda (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Cow’s feces originated from farms dairy an organic waste that can causing an environmental pollutiontherefore need to be process to make something such as fertilizer using activators that help the decompositionprocess run faster. Activator used in this experiment is Stardec. Decomposition of cow’s feces becomingorganic fertilizer by mixing cow’s feces with Stardec activator. Ratio of cow’s feces weight (Metric Ton) byweight (Kilogram) of Stardec activator is 1:0; 1:1; 1:2; 1:3; 1:4. Thereafter, add the anorganic fertilizer(Urea, KCl, SP-36) and limestone to the mixture each about 2,5 kilograms after that cover the mixture withplastic wrap and make some holes with bamboo. The allowing the mixture for 3 weeks to make an analysis ontemperature and C/N ratio for 3 days. The experiment result shows that process of composition for 21 dayson Stardec with 10 kg weight to produce organic fertilizer consist about 15,23% organic carbon, 0,84% totalnitrogen, 18,13 C/N ratio. These result meet the quality standards set by the Minister of AgricultureNo.70/Permentan/SR.140/10/2011.